The Role of Agribusiness Competencies in Strategic Decision-Making for Millennial Farmers in Kubu Raya Regency (Jurnal AGRISEP: Kajian Masalah Sosial Ekonomi Pertanian dan Agribisnis, 2025)
Millennial farmer' management decisions are influenced by their agribusiness competencies. Farmers are constantly faced with decision-making on what and how to produce it. Both controllable internal and uncontrollable external factors constrain farmers' decision-making process. Meanwhile, millennial farmers will need to act as the driving force of agriculture in the future. Millennial farmers require sufficient agribusiness skills to manage their farms effectively. This study examines the competencies of millennial farmers in agribusiness, their managerial decision-making process, and the relationship between these competencies and organizational decisions. The agribusiness competency variables studied are based on agribusiness subsystems, including input supply, production process, product processing, marketing, and supporting subsystems. This study included all millennial farmers in Kubu Raya Regency. The sample was determined to be 150 samples using purposive sampling. A selected sample of millennial farmers aged 19-39 years old. The analysis used interval class category analysis with three categories: good, moderate, not good, and Spearman rank correlation analysis. Results of the analysis show that millennial farmers have moderate agribusiness competencies and managerial decision-making processes. There is a strong positive correlation between agribusiness competencies and managerial decision-making processes. The government should enhance millennial farmers' agribusiness skills by providing infrastructure, facilities, and marketing, finance, and product processing training while collaborating with academics to develop technology and innovation.